Post traumatic hepatic artery pseudoaneurysm: a tertiary care centre experience - Gopal, Prasanna; Subbarayan, Shankar; Mohan, Karthikeyan; Anbalagan, Amudhan; S., Kalpana; Shanmugasundaram, Rajendran; Moorthy, Naganath Babu Obla Lakshmana (International Surgery Journal, 2019)
In blunt trauma abdomen, liver is the most commonly injured organ after spleen. Management of blunt hepatic injury has shifted from operative to non-operative management NOM in hemodynamically stable patients. Main cause of failure of NOM is hemodynamic instability due to re-bleeding or secondary hemorrhage due to rupture of capsular hematoma. Post traumatic hepatic artery pseudoaneurysm HAP as a cause of failure of NOM is rare, reported in about 1.2%. HAP requires early intervention by angiographic embolisation or surgery to prevent catastrophic event. Here, we report our experience with four cases of HAP managed in our centre in past three years. Three patients were managed by selective angioembolisation and one patient was treated by surgery. All patients had uneventful recovery and are asymptomatic on follow-up. HAP is a rare life threatening complication which can present even after successful NOM as a delayed presentation. All symptomatic pseudoaneurysm has to be managed by angioembolisation or surgery depending on hemodynamic stability.